Role of Anions in the Synthesis and Crystal Growth of Selected Semiconductors - Matussin, Shaidatul Najihah; Rahman, Ashmalina; Khan, Mohammad Mansoob (Frontiers in Chemistry, 2022)
The ideal methods for the preparation of semiconductors should be reproducible and possess the ability to control the morphology of the particles with monodispersity yields. Apart from that, it is also crucial to synthesize a large quantity of desired materials with good control of size, shape, morphology, crystallinity, composition, and surface chemistry at a reasonably low production cost. Metal oxides and chalcogenides with various morphologies and crystal structures have been obtained using different anion metal precursors (and/or different sulfur sources for chalcogenides in particular) through typical synthesis methods. Generally, spherical particles are obtained due as it is thermodynamically favorable. However, by changing the anion precursor salts, the morphology of a semiconductor is influenced. Therefore, precursors having different anions show some effects on the final forms of a semiconductor. This review compiled and discussed the effects of anions (NO3-, Cl-, SO42-, CH3COO-, CH(CH3)O-, etc.) and different sources of S2- on the morphology and crystal structure of selected metal oxides and chalcogenides.